Synthesis and Characterization of Efficient Adsorbents for Methylene Blue Based on Graphene Oxide/β-cyclodextrin Composites - Yanping, Qu; Hongcui, Li; Ibrahim, Yakub; Wen, He; Wenchan, Dong; Mohamad Hardyman, Barawi; Sirui, Wang; Huimin, Ma; Zhenpeng, Zhu (Springer, 2025)
In this paper, a novel graphene oxide/β- cyclodextrin composite (GO/β-CD) adsorbent was synthesized for the effective simultaneous removal of dyes. GO and GO/β-CD were characterized using BET, SEM, FT-IR, Raman, and XRD techniques. GO/β-CD has a BET specific surface area of 0.25 m2/g. The surface of GO/β-CD contains a significant number of reactive groups, such as carboxyl groups, which enable the effective adsorption of methylene blue (MB). The adsorption of GO/β-CD on methylene blue (MB) in aqueous solution was also investigated kinetically and thermodynamically. The kinetic and thermodynamic parameters of the reaction were calculated. Based on the experimental results, the adsorption reaction was determined to be a spontaneous endothermic reaction. The adsorption of MB on GO/β-CD best fit the Langmuir model based on the results of the adsorption isotherm model fitting. The maximum adsorption capacity of the composite was 434.78 mg/g. The GO/β-CD adsorbent was highly efficient at adsorbing cationic dyes, and its performance remained consistently high after six cycles. Thus, GO/β-CD offers the advantages of nontoxicity, excellent adsorption and regeneration properties, and great potential for treating real and simulated wastewater from various industries.